Peranan Environmental Accounting terhadap Global Warming - Riki Martusa (Universitas Kristen Maranatha, 2009)
This article explores about is global warming. The distortion of nature causes global warming. Industrial sector is one of global warming incurred. Some nations create a group to cope this matter. They try to reduce carbon emission as one of global warming causes by controlling industrial carbon emission through financial reporting. This article explores normatively roles of environmental accounting in cope with global warming. Keywords: global warming and environmental accounting.